INFLUENCE OF DIFFERENT PERFORMANCE OF ANTI-YAW DAMPER ON VEHICLE DYNAMICS - SHAO JunJie; LEI Lei; HU ZeYao (Jixie qiangdu)
Anti-yaw damper is a key component of high-speed train suspension system. In this paper, through the measured performance degradation data of anti-yaw damper and the damping value setting of anti-yaw damper, the performance data of anti-yaw damper in different states are obtained. According to the dynamic parameters of a certain high-speed train in China, the dynamic model of the vehicle is established, and the influence on the dynamic performance of the vehicle is analyzed based on the performance data of anti-yaw damper in different performance states.The results show that: In actual operation, the performance change of anti-yaw damper has little effect on the force between wheel and rail; In the actual operation, the performance change of anti-yaw damper has a certain impact on the running stability of the vehicle, but the impact degree is limited. Under the simulation condition, the vehicle’s stability is always in a better state; The critical speed of the vehicle operation is sensitive to the performance change of anti-yaw damper.The simulation results of the measured performance degradation data show that with the use of anti-yaw damper, the critical speed of the vehicle decreases significantly; the simulation results of the damping value setting of anti-yaw damper show that appropriate increase of damping value is conducive to increase the critical speed of vehicle operation and improve the stability of vehicle operation.